Role of somatostatin in the prevention of pancreatic reactions in patients undergoing endoscopic retrograde cholangio-pancreatography (ERCP) - , Yusuf UZUN, Necati ÖRMECİ and , Selim KARAYALÇIN and , Cihan YURDAYDIN and , Ali Reşit BEYLER and , Özden UZUNALİMOĞLU and , Abdülkadir DÖKMECİ (Turkish Journal of Gastroenterology 1, 2019)
-